Model Pembelajaran Pendidikan Agama Kristen Berbasis Digital Untuk Generasi Alfa di Era Society 5.0 - Ludia Wisalen Soukotta; Yuliana Souhaly (Institut Agama Kristen Negeri (IAKN) Ambon, 2025)
Abstract: This study aims to examine a digital-based model of Christian Religious Education that is relevant for Generation Alpha in the era of Society 5.0, considering the characteristics of this generation who grow up in a digital technology environment with interactive, visual, and dynamic learning styles. The method used is a qualitative approach through a literature study of various relevant scientific sources. The findings show that digital-based learning can enhance students’ learning interest, active participation, and understanding of spiritual values. An effective learning model includes the use of interactive media, project-based learning, and the integration of technology such as learning applications and digital platforms. In addition, the role of teachers remains a key factor as facilitators and spiritual mentors in guiding meaningful learning processes. Thus, it can be concluded that a digital-based model of Christian Religious Education is highly relevant and effective for Generation Alpha in shaping character and faith in the era of Society 5.0. Keywords: Christian Religious Education, digital learning, Generation Alpha, Society 5.0, learning model